Assessing the Risk and Needs of Supervised Sexual Offenders: A Prospective Study Using STABLE-2007, Static-99R, and Static-2002R. (December 2015) - Hanson, R. Karl; Helmus, Leslie-Maaike; Harris, Andrew J. R.
Effective intervention with offenders requires accurate identification of their risk-relevant propensities. In this prospective study, 139 Canadian community supervision officers were trained to assess the risk factors and criminogenic needs of adult male sexual offenders using structured risk tools. Recidivism outcomes were recorded for 768 offenders (average age of 41 years, approximately half had child victims, 14% Aboriginal) during an average 7-year follow-up period. All forms of recidivism (sexual, violent, any) were predicted by sex crime specific risk tools based on static, historical factors (Static-99R; Static-2002R) and by tools designed to assess psychologically meaningful risk factors of sexual offenders (STABLE-2000; STABLE-2007). Professional overrides of the Static-99 scores did not improve predictive accuracy. STABLE-2007 scores added incrementally over STATIC scores for all recidivism outcomes, but only for complete cases, suggesting meaningful variation in the extent to which community supervision officers can assess psychologically meaningful risk factors for sexual offenders.